Quality Assessment of Milk Powders Packed in Sudan - El Khier, Murwan Khalid Sabah; A. Yagoub, Abu El Gasim (Pakistan Journal of Nutrition, 2009)
Physicochemical, microbiological and sensory characteristics of milk powders packed in Sudan were investigated and compared with international quality standards. The compositions (moisture, fat, protein, ash and lactose) of the locally packed milk powders are almost insignificantly different (p<0.05) and they are comparable to the compositional quality in US and Argentina. Despite the significant (p<0.05) variations in acidity and pH between milk powder samples, their levels remained within the acceptable standard levels. Results also showed that most milk powders packed in Sudan had partial solubility in water, in comparison with the instantly soluble standards. Microbiologically the samples were safe, but organoleptically they considered of fair quality.